En kur mod bændelorm og gallomani: Intra-europæisk ‘occidentalisme’ i den russiske 1700-talsforfatter Denis Fonvizins komedie Brigaderen og hans rejsebreve fra Frankrig - Møller, Peter Ulf (K&K - Kultur og Klasse, 2009)
A Cure for Tapeworm and Gallomania: Intra-European ‘Ocidentalism’ in the Russian Comedy The Brigadier by Denis Fonvizin and in his Travel Letters from France: Is Europe destined to remain a unit without unity, because of its endlessly differentiated cultural patterns and its divided, centrifugal past? This question seems to emerge as the bottom line of Hans Magnus Enzensberger’s observations from seven European countries, in his famous Ach Europa from 1987. In the microstructure of the disunity, we find national stereotypes as an element of intra-European discourses. Roman Jakobson discussed the complex of intra-European reciprocal images from a structuralist point of view. He proposed a systematic study of »national characterology« as an element in the discourses and mentalities of the various European nations. Inspired by both of these works, the present article is a minor investigation into a major area within intra-European relations, namely the east-west divide. It discusses two works by the Russian 18th century writer Denis Fonvizin, his comedy The Brigadier and his travel letters from France. Both are anti-western classics in Russian literature, greatly appreciated by conservative nationalists in Fonvizin’s days, and later famously applauded by Dostoyevsky. However, for both works it turns out, somewhat paradoxically, that Fonvizin took inspiration from the arsenals of newly imported European ideas and literature. The travel letters offer several examples of stereotypical negative characterisations from Western travel writing about Russia now being used by Fonvizin to describe the French. Holberg’s comedy Jean de France was popular on the Russian stage, and Fonvizin transferred the frenchified fop to a Russian setting with great success. Both of his works became tools for a budding Russian »Occidentalism« of the intra-European kind.